An improved technique for zygoma reduction malarplasty. Issue 4 (April 2018) - Kim, Jae Jin; Lee, Eun Young; Seok, Hyun; Kang, Ji Yeon
Abstract: Zygoma reduction malarplasty is a standard procedure primarily performed in Asia on patients who prefer an oval facial shape. The technique is well established and standardized. However, the esthetic results are frequently unsatisfactory or accompanied by complications such as nonunion, malunion, and cheek drooping. These complications are generally attributed to postoperative bone fragment movement. In this study, we present an improvement to this standard procedure that involves modifying the surgical technique. With our suggested modification, the chance of displacement is decreased because of increased locking resulting from greater surface-to-surface contact between the posterior bone segments. Moreover, the prominence of the anterior zygoma is maintained, whereas posterior zygoma width is slightly decreased. In our technique, fixation is performed only in the zygoma body area, and posterior fixation can be avoided. In addition, in cases where fixation is not performed, the protrusion of the posterior aspect of the articular tubercle can be decreased by grinding. We believe that the modified technique has the potential to markedly improve the treatment outcomes of zygoma reduction malarplasty.